The effect of referral to an open‐group behavioural weight‐management programme on the relative risk of normoglycaemia, non‐diabetic hyperglycaemia and type 2 diabetes: Secondary analysis of the WRAP trial. Issue 11 (15th July 2020) - Ahern, Amy L.; Griffin, Simon J.; Wheeler, Graham M.; Sharp, Stephen J.; Aveyard, Paul; Boyland, Emma J.; Halford, Jason C. G.; Jebb, Susan A.
Abstract: Aim: To examine the impact of open‐group behavioural weight‐management programmes on the risk of diabetes among those with a body mass index (BMI) of ≥28 kg/m 2 and those with non‐diabetic hyperglycaemia (NDH). Methods: This was a secondary analysis of data from the WRAP trial, in which participants (N = 1267; aged ≥18 years, BMI ≥ 28 kg/m 2 ) were randomized to brief intervention (BI; self‐help booklet), a weight‐management programme (WW; formerly Weight Watchers) for 12 weeks, or WW for 52 weeks. We used multinomial logistic regression to examine the effect of intervention group on the risk of hyperglycaemia and diabetes at 12 months in all participants with glycaemic status at both time points (N = 480; 38%) and those with NDH at baseline (N = 387; 31%). We used mixed effects models and linear fixed effects models to examine the effect of intervention group on body weight and HbA1c at 12 months in people with NDH. Results: There was a 61% relative reduction in the risk of NDH at the 12‐month follow‐up (12 weeks vs. BI: relative risk ratio [RRR] = 0.39 [95% CI 0.18, 0.87], P = .021; 52 weeks vs. BI: RRR = 0.38 [95% CI 0.17, 0.86], P = .020). For intervention effects on the risk of diabetes, confidence intervals were wide and overlapped 1 [12 weeks vs. BI: RRR = 0.49 [95% CI 0.12, 1.96], P = .312; 52 weeks vs. BI: RRR = 0.40 [95% CI 0.10, 1.63], P = .199). Participants with hyperglycaemia at baseline in the weight‐management programme were more probable to have normoglycaemia at the 12‐month follow‐up [12‐week programme vs. BI: RRR = 3.57 [95% CI 1.24, 10.29], P = .019; 52‐week programme vs. BI: RRR = 4.14 [95% CI 1.42, 12.12], P = .009). Conclusions: Open‐group behavioural weight‐management programmes can help to prevent the development of NDH in people with overweight and obesity and to normalize glycaemia in people with NDH.